Relação dos antirretrovirais com as alterações lipídicas da síndrome lipodistrófica em pessoas vivendo com HIV/AIDS - Rodrigues, Brenda Feitosa Lopes (2021)
Withtheintroductionof ART, therewasanimprovement in thequalityoflifeof PLWHA, as well as a change in themorbidityandmortality profile. However, byincreasingthelifeexpectancyofpeople living with HIV/AIDS (PLHA), the use ofantiretroviraltherapybrought some complications for thesepeopleregardingdyslipidemia. Objective: Toanalyzetherelationshipofantiretroviralswithlipidalterationsoflipodystrophicsyndrome in people living with HIV/AIDS. Method: Thisis a cross-sectionalstudybasedon data collectedbytheNutricárdio Project from 03/25/2015 to 05/30/2016. The data collection site wasthe Clementino Fraga InfectiousDiseases Hospital Complex (CHCF), a reference hospital in pvhacare, in themunicipalityof João Pessoa - PB. The populationofthisstudywasestimated in 2861 individualswhoregularlyreceived ART in theservice, andthe sample wascomposedof 400 PLWHA, amongthesetherewere some losses in the follow-up ofthevariables '' dyslipidemia '' and '' typesofdyslipidemia '' justifyingthevariationofthe sample in some cases. In theseindividualswillbedescribedtheriskassociatedwiththe use of ART for thedevelopmentofDyslipidemia, whichwillbethedependentvariable. The WOE Model wasapplied, whichevaluatedtheinfluenceofthe use ofantiretroviralsonthedependentvariabledyslipidemia. Aftertheanalysis, data regardingthesociodemographic profile of PLWHA withdyslipidemia, thetypeof ART usedandtheassociationbetweenbothwerepresentedthroughtablesandgraphs. Results: Regardingsociodemographicvariablesof PLWHA amongthosewithdyslipidemia, therewas a slightprevalence, male (60.0%), non-white (66%), comprising age group, 50% ofpeoplewereaged>45 yearsand 50% wereaged ≤ 45 years.Schoolingwascharacterizedby a discretemajorityuntilincompleteelementaryschool (57%), regardingtheaffectivesituation, 54% do notlivewith a partner, 33% have per capita income at 1 minimumwageand 54% have as occupation, retired/pensioner. It wasobservedthatwhenthesociodemographicvariableswerenotsignificantdifference for PLWHA withdyslipidemiaandwithoutdyslipidemia. Regardingthe profile ofantiretroviral use, therewas a predominance (30.8%) combination for group II (AZT/3TC+Protease Inhibitor (IP)). As for THE PLWHA in the use of ART, 179 (54.9%) whopresenteddyslipidemia, used ART with PI, as well as, it wasobservedthatamongthe 108 PLWHA usingthecombinationreferredto in group II, therewas a higherprevalenceofdyslipidemia (88.5%). Regardingthetypeofdyslipidemiaof PLWHA using ART with PI, 70 (39.1%) presentedhypertriglyceridemiaandlow HDL andwhenassociatedwiththevariablereferringtothemostused ART groups, whousedgroup II alsopresentedHypertriglyceridemiaandlow HDL 39 (35.8%). Finally, throughthe WOE it waspossibletoverifytheweightofevidence in dyslipidemiaby ART groups, concludingthat ART has a weakinfluenceondyslipidemia, whichisextremelyrelevanttounderstandthattheriskof a PLWHA developingdyslipidemiaisnotlimitedonlytothefactthat it uses ART, andthere are otheraspectsthatmaymodifythis profile. It isnotepointthatthestudywillhaveaneffectonallpublichealth, fromthemoment, whichcan help thehealth professional toexpandtheirknowledgeaboutthe cause ofdyslipidemia, emphasizingthatthe use of ART isnottheonlyfactorto trigger it.